Experimental diabetes alters the morphology and nano-structu re of the achilles tendon - Oliveira, Rodrigo Ribeiro de (2017)
Although of several studies that associate chronic hyperglycemia with tendinopathy, the connection between morphometric changes as witnessed by magnetic resonance (MR) images, nanostructural changes, and inflammatory markers have not yet been fully established. Therefore, the present study has as a hypothesis that the Achilles tendons of rats with diabetes mellitus (DM) exhibit structural changes. The animals were randomly divided into two experimental groups: Control Group (n = 06) injected with a vehicle (sodium citrate buffer solution) and Diabetic Group (n = 06) consisting of rats submitted to intraperitoneal administration of streptozotocin. MR was performed 24 days after the induction of diabetes and images were used for morphometry using ImageJ software. Morphology of the collagen fibers within tendons was examined using Atomic Force microscopy (AFM). An increase in the dimension of the coronal plane area was observed in the diabetic group (8.583 ± 0.646 mm2/100g) when compared to the control group (4.823 ± 0.267 mm2/100g) resulting in a significant difference (p = 0.003) upon evaluating the Achilles tendons. Similarly, our analysis found an increase in the size of the transverse section area in the diabetic group (1.328 ± 0.103 mm2/100g) in comparison to the control group (0.940 ± 0.01 mm2/100g) p = 0.021. The tendons of the diabetic group showed great irregularity in fiber bundles, including modified grain direction and jagged junctions and deformities in the form of collagen fibrils bulges. Despite the morphological changes observed in the Achilles tendon of diabetic animals, IL1 and TNF-α did not change. Our results suggest that DM promotes changes to the Achilles tendon with important structural modifications as seen by MR and AFM, excluding major inflammatory changes.